The Development of Earthquake Simulator - Nur Azhary Iriawan Eka Putra; Rafiuddin Syam; Ilyas Renreng; Tri Harianto; Nanang Roni Wibowo (EPI International Journal of Engineering, 2021)
An earthquake is an event that vibrates or shakes the earth due to the sudden movement or shift of rock layers on the earth's crust due to the movement of tectonic plates. Earthquakes that occur cause damage to buildings and loss of life and can trigger other natural disasters such as tsunamis and even liquefaction. To anticipate this, it is necessary to study the structure of the building and tools to test the strength of the building, so that it becomes an effective tool and is needed to anticipate the occurrence of large losses. The earthquake simulator was built in the form of a shaking table driven by a hydraulic actuator. The earthquake simulator is equipped with a proximity sensor to determine the cylinder motion distance which is controlled using proportional and integral using the Arduino Mega2560 controller. The results showed that the shaking table can work ideally with a value of P (kc) = 0.066195 and a value of I (ki) = 2.009974 which can produce acceleration data in actual (real-time) which is displayed in graphical form on the LabVIEW front panel.